PRESIDENTIAL CANDIDATES™ SPEECH ON YOUTUBE: A VIEW OF METAPHORICAL - Br. Karo, Anggina Mayla Yasi (Universitas Negeri Medan, 2023)
Indonesia is currently facing the political issues, including the election of potential Presidential candidates for the period of 2024 to 2029. This study aims to find out the types of metaphor used by the three of Indonesian presidential candidates and are the metaphor used by presidential candidates™ speech on YouTube. This study applied qualitative research method as the design in the analyzing the data. The study subject were three Indonesian presidential candidates with the data from the utterances according to three Indonesian presidential candidates™ speeches. The source of the data was taken from three Indonesian presidential candidates in Bicara Gagasan-Mata Najwa youtube channel for Indonesia election 2024. The findings showed that three types of metaphor used by the three Indonesian presidential candidates are structural metaphor, oriental metaphor and ontology metaphor. The three types of metaphor used by Indonesian presidential candidates on their speech such as; structural metaphor was about 7 (53.8%), orientational metaphor was about 2 (15.4%) and ontology metaphor around 4 (30.8%). The most dominant types of metaphor used by Indonesia presidential candidates in the Indonesia election 2024 is structural metaphor. Meanwhile, the reasons of Indonesian presidential candidates used metaphor on their speech were for directing and limiting the audience's understanding. Political speeches benefit from the use of metaphors, which clarify complex concepts through physical experiences and sensory explanations.